Giant Baker’s Cyst Associated with Rheumatoid Arthritis - Levent Adiyeke; Emre Bılgın; Tahir Mutlu Duymus; İsmail Emre Ketencı; Meriç Ugurlar (Case Reports in Orthopedics)
We report a rare case of a “giant Baker’s cyst-related rheumatoid arthritis (RA)” with 95 × 26 mm dimensions originating from the semimembranosus tendon. The patient presented with chronic pain and a palpable mass behind his left calf located between the posteriosuperior aspect of the popliteal fossa and the distal third of the calf. In MRI cystic lesion which was located in soft tissue at the posterior of gastrocnemius, extensive synovial pannus inside and degeneration of medial meniscus posterior horn were observed. Arthroscopic joint debridement and partial excision of the cyst via biomechanical valve excision were performed. The patient continued his follow-up visits at Rheumatology Department and there was no recurrence of cyst-related symptoms in 1-year follow-up. Similar cases were reported in the literature previously. However, as far as we know, a giant Baker’s cyst-related RA, which was treated as described, has not yet been presented.